2022
DOI: 10.3390/jcm11072031
|View full text |Cite
|
Sign up to set email alerts
|

The Osteosynthesis of the Mandibular Head, Does the Way the Screws Are Positioned Matter?

Abstract: Currently, an increasing number of medical centers are treating mandibular head fractures surgically. Dedicated screws for compression osteosynthesis have been developed. However, due to the very limited size of the fractured bones and the considerable technical difficulties accompanying the execution of the fixation, there is little room for correction of the positioning and reinsertion of the screws. Therefore, knowing the optimal position of the fixation material is crucial for therapeutic success. The aim … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…It should be noted here that the analgesic efficacy of intra-articular PRP injections is based on the correct identification of joint pain and distinguishing it from ailments of myofascial origin, which can also be treated but with other methods [ 1 , 4 , 19 , 20 , 21 ]. Limits in the mobility of the mandible suitable for injection therapy should, in turn, be differentiated from mechanical obstacles resulting from fractures with blockage of the fragments, misplacement of the osteosynthetic material, and the consequences of injuries including ankylosis [ 22 , 23 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted here that the analgesic efficacy of intra-articular PRP injections is based on the correct identification of joint pain and distinguishing it from ailments of myofascial origin, which can also be treated but with other methods [ 1 , 4 , 19 , 20 , 21 ]. Limits in the mobility of the mandible suitable for injection therapy should, in turn, be differentiated from mechanical obstacles resulting from fractures with blockage of the fragments, misplacement of the osteosynthetic material, and the consequences of injuries including ankylosis [ 22 , 23 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mandibular head fractures are important to consider, as different injury mechanisms demand various therapeutic modalities, a treatment method being the surgical approach, in which compression osteosynthesis-specific screws have been created. The therapeutical success depends on the location of the fracture and on knowing where to place the fixation due to the small size of the fractured bones [43]. Kozakiewicz et al stated that despite the publication of 30 plate designs, no information on plates for low-neck mandibular condylar osteosynthesis can be found, therefore the authors compared different types of specialized plates that might be used in low-neck condylar fracture osteosynthesis [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…The therapeutical success depends on the location of the fracture and on knowing where to place the fixation due to the small size of the fractured bones [43]. Kozakiewicz et al stated that despite the publication of 30 plate designs, no information on plates for low-neck mandibular condylar osteosynthesis can be found, therefore the authors compared different types of specialized plates that might be used in low-neck condylar fracture osteosynthesis [43,44]. In their study of low-neck mandibular condylar osteosynthesis plates, the authors found that one should either take into account the mechanical benefits when selecting a plate for open rigid internal fixation in low-neck condylar fractures, or one should only be aware of the notable variations in mobility within the fracture line after fixation with different specialized plates [44].…”
Section: Discussionmentioning
confidence: 99%
“…This texture feature describes thick, uniformly dense, radio-opaque bone structures in intraoral radiograph images [4,12]. The equations for DifEntr and LngREmph were subsequently used for the index construction [4][5][6]12]. The bone index (BI), which represents the ratio of the diversity of the structure observed in the radiograph to the measure of the presence of uniform longitudinal structures, was calculated:…”
Section: Methodsmentioning
confidence: 99%
“…The author suspects that low BIs occur not only in images of cortical and corticalized bone but also in areas of bone atrophy (uniformly radiologically translucent). This suspicion is related to the structure of the BI [4,6] since there is a measure in its structure that highlights the existence of long strings of pixels of similar brightness (in other words, of similar radiographic translucency). This measure is not related to high brightness (optical density) only but shows both high and low optical density regions.…”
Section: Introductionmentioning
confidence: 99%